Analysis of cat-friendly furniture in the context of the relationship between space, furniture and user in housing units - KOÇ SAĞLAM, CEREN (My University, 2020)
nd animals reshaped common living areas. By taking into consideration the factors such as the ease of establishing ties, ease of care and physical advantages, human beings prefer having cats more often as pets in order to live together in their own common living areas. The furniture is one of the important tools which satisfy cats’ needs such as establishing relations and communicating with human beings, strengthening ties between themselves & human beings and creating a safe zone for themselves. Cat-friendly furniture is the piece of furniture which is designed to allow the cat and/or human being to meet their needs and to perform their activities on a daily basis. In this study, the furniture utilized in housing units was analyzed as it acted as the place where human being and cat spent most of their time together. Furniture was analyzed under four categories in terms of the purpose of its uses in the housing unit (self-care/activity), its relationship with the space (fixed/mobile), its relationship with the user (common/single use) and the mode of production of the design (special fabrication/mass-production). In terms of the purpose of uses of furniture, the study addressed compulsory forms of furniture by which cat could satisfy its self-care needs such as nourishment, toilet and scratching and evaluated pieces of furniture equipped with alternative functions through which the cat could enjoy activities such as playing games, sleeping, climbing and hiding. Upon the examination of the relationship of furniture with the space in which it existed, the furniture was categorized as fixed and mobile. Moreover, upon the review of the relationship of furniture with the user, the furniture was categorized into two groups as common use and single use furniture on the basis of its joint use by human being and cat. As per the mode of production, it was discerned that the furniture was designed to be specialfabrication and mass-production on the basis of basic needs, forms, aesthetics and spatial harmony concerns. In this connection, by examining samples of furniture in terms of above four categories identified in the context of this study, the study aimed to analyze the effect of cat-friendly furniture on furniture design in housing units at the intersection of human being, cat and space.
Keywords: User; furniture; cat; house; furniture design